Controlled self-assembly of plant proteins into high-performance multifunctional nanostructured films - Ayaka Kamada; Marc Rodriguez-Garcia; Francesco Simone Ruggeri; Yi Shen; Aviad Levin; Tuomas P. J. Knowles (Nature Communications, 2021)
Green use of plant derived proteins in functional materials has been limited by inefficient methods to control micro and nanoscale structure. Here, the authors use nanoscale assembly of water-insoluble plant proteins to make meter scale films with comparable properties to conventional plastics.